Drawing and Experiencing Architecture The Evolving Significance of City's Inhabitants in the 20th Century - Charitonidou, Marianna (Architekturen, 2022)
How were the concepts of the observer and user in architecture and urban planning transformed throughout the 20th and 21st centuries? Marianna Charitonidou explores how the mutations of the means of representation in architecture and urban planning relate to the significance of city's inhabitants. She investigates Le Corbusier and Ludwig Mies van der Rohe's fascination with perspective, Team Ten's interest in the humanisation of architecture and urbanism, Constantinos Doxiadis and Adriano Olivetti's role in reshaping the relationship between politics and urban planning during the postwar years, Giancarlo De Carlo's architecture of participation, Aldo Rossi's design methods, Denise Scott Brown's active socioplactics and Bernard Tschumi's conception praxis.